Atrial fibrillation after coronary bypass graft - what do we know now? - Adriana Misiło; Monika Sosna; Krzysztof Mordoń (Kazimierz Wielki University, 2023)
Introduction: Atrial fibrillation (AF) is the most common supraventricular arrhythmia in clinical practice. The percentage of people with AF increases with age. The currently implemented procedure for detecting modifiable risk factors allows for early implementation of a therapeutic plan in primary and secondary prevention. The following work deals with the occurrence of atrial fibrillation, risk factors and ways of coping with the disease in patients undergoing coronary artery bypass grafting (CABG). Materials and methods: The literature available on PubMed and Google Scholar was reviewed using the words "atrial fibrillation", "coronary artery bypass grafting". Summary: Patients undergoing coronary artery bypass surgery are at risk of developing postoperative atrial fibrillation. This is especially true for older patients with additional burdens, such as past arrhythmia episodes, hypertension, critical stenosis of the right coronary artery.